2014
DOI: 10.1126/science.1256337
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimidoindole derivatives are agonists of human hematopoietic stem cell self-renewal

Abstract: The small number of hematopoietic stem and progenitor cells in cord blood units limits their widespread use in human transplant protocols. We identified a family of chemically related small molecules that stimulates the expansion ex vivo of human cord blood cells capable of reconstituting human hematopoiesis for at least 6 months in immunocompromised mice. The potent activity of these newly identified compounds, UM171 being the prototype, is independent of suppression of the aryl hydrocarbon receptor, which ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
485
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 494 publications
(499 citation statements)
references
References 18 publications
9
485
0
5
Order By: Relevance
“…No adverse effects were observed with the infusion of NiCord. NiCord engraftment remained stable in patients, and the patients who received the NAM-treated culture achieved earlier median neutrophil [190] AhR antagonist (SR1) phase I/II trial enhances neutrophil recovery antagonizing an acryl hydrocarbon receptor [191][192][193] PGE2 2 h phase I trial enhances neutrophil recovery enhancing homing, survival, and proliferation of HSCs [65,194,195] TPO receptor agonist (NR-101) 7 d repopulation 2.9-fold activating STAT5 and Hif-1alpha [197] UM171 12 d repopulation 13-fold inhibiting erythroid and megakaryocytic differentiation [192] recovery than those given untreated cord blood [190]. EX-527, another SIRT1 inhibitor, also inhibits differentiation of human CD34 + cells [189].…”
Section: Sirtuin 1 (Sirt1) Inhibitormentioning
confidence: 99%
See 3 more Smart Citations
“…No adverse effects were observed with the infusion of NiCord. NiCord engraftment remained stable in patients, and the patients who received the NAM-treated culture achieved earlier median neutrophil [190] AhR antagonist (SR1) phase I/II trial enhances neutrophil recovery antagonizing an acryl hydrocarbon receptor [191][192][193] PGE2 2 h phase I trial enhances neutrophil recovery enhancing homing, survival, and proliferation of HSCs [65,194,195] TPO receptor agonist (NR-101) 7 d repopulation 2.9-fold activating STAT5 and Hif-1alpha [197] UM171 12 d repopulation 13-fold inhibiting erythroid and megakaryocytic differentiation [192] recovery than those given untreated cord blood [190]. EX-527, another SIRT1 inhibitor, also inhibits differentiation of human CD34 + cells [189].…”
Section: Sirtuin 1 (Sirt1) Inhibitormentioning
confidence: 99%
“…SR1 does not support ex vivo expansion of mouse HSCs or adult human HSCs [182]. Recently, it was suggested that SR1 acts on cells with limited self-renewal potential but that it does not support proliferation of the most primitive HSCs [192]. A phase I/II clinical trial is ongoing and early results indicate that the SR1-containing culture system significantly enhances neutrophil recovery after transplantation [193].…”
Section: Stemregenin 1 (Sr1)mentioning
confidence: 99%
See 2 more Smart Citations
“…Contrary to any unrelated donor cell, UCB is collected without any risk and non-invasively which can be cryopreserved for longer time without the loss of basic features like cell viability, functionality and have lower risk to transfer viral infections and mutations which causes complications to the patient after transplantation [25,26]. Disadvantage of UCB includes cell dosage and delayed engraftment which are the main hurdles and the conventional UCBrelated treatment have restrictions whenever receivers are more and patients with known resistant to engraftment due to lower hematopoietic per UCB unit [25,[27][28][29][30].…”
Section: Cord Blood For Regenerative Medicinementioning
confidence: 99%